MetaLanc9 as a novel biomarker for non-small cell lung cancer: promising treatments via a PGK1-activated AKT/mTOR pathway - De Mello, Ramon Andrade; Aguiar, Pedro Nazareth; Tadokoro, Hakaru; Farias-Vieira, Tállita Meciany; Castelo-Branco, Pedro; de Lima Lopes, Gilberto; Pozza, Daniel Humberto (Journal of Thoracic Disease, 2018)
Non-small cell lung cancer (NSCLC) is still challenging in terms of screening and treatment approaches (1). In Europe, Latin-America and US, NSCLC is among the most common diseases for both men and women (2).